Looking at Kaposi’s Sarcoma-Associated Herpesvirus–Host Interactions from a microRNA Viewpoint - Liang, Deguang; Lin, Xianzhi; Lan, Ke (Frontiers in Microbiology, 2012)
Kaposi’s sarcoma-associated herpesvirus (KSHV), also called human herpesvirus 8, belongs to the gamma herpesviruses and is the etiological agent of Kaposi’s sarcoma, primary effusion lymphoma and some types of multicentric Castleman’s disease. In vivo, KSHV mainly infects B cells and endothelial cells. The interactions between KSHV and its host cells determine the outcome of viral infection and subsequent viral pathogenesis. MicroRNAs (miRNAs) are small, noncoding RNAs that are important in fine-tuning cellular signaling. During infection, KSHV modulates the expression profiles or functions of a number of host miRNAs, for example hsa-miR-132 and hsa-miR-146a. KSHV encodes 12 pre-miRNAs, including miR-K12-11, which is the functional ortholog of the host miR-155. A number of cellular and viral targets of deregulated cellular miRNAs and viral miRNAs are found in KSHV-infected cells, which suggests that miRNAs maybe important in mediating KSHV-host interaction. In this review, we summarize our current understanding of how KSHV modulates the expression and function of host miRNAs; we review in detail the functions of miR-K12-11 as the ortholog of miR-155; and we examine the functions of viral miRNAs in KSHV life cycle control, immune evasion, and pathogenesis.